2014
DOI: 10.2147/cia.s60555
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of external valvuloplasty in adult patients with isolated great saphenous vein insufficiency

Abstract: ObjectiveThe aim of this study is to present our 7-year results of external valvuloplasty for isolated great saphenous vein (GSV) insufficiency.MethodsExternal valvuloplasty was applied in 83 patients with isolated GSV insufficiency. Follow-up consisted of venous color duplex scanning performed on the first postoperative day, the first postoperative month, and then annually. Valvular insufficiency, venous reflux, and venous thrombosis formation in the saphenofemoral junction were the main outcomes.ResultsA com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“… 17 Sarac et al. 18 also found a decreased diameter of the great saphenous vein at the saphenofemoral junction. The authors described a significant reduction from 5.6 mm preoperatively to 3.1 mm postoperatively on the first postoperative day.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“… 17 Sarac et al. 18 also found a decreased diameter of the great saphenous vein at the saphenofemoral junction. The authors described a significant reduction from 5.6 mm preoperatively to 3.1 mm postoperatively on the first postoperative day.…”
Section: Discussionmentioning
confidence: 91%
“…Seven years after the treatment, the authors reported a mean diameter at the saphenofemoral junction of 4.5 mm, but did not state the significance level. 18 Geier et al. 15 measured the diameter of the great saphenous vein in their study with a 5-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations